The second machine age work, progress, and prosperity in a time of brilliant technologies - Brynjolfsson, Erik. (New York W. W. Norton & Company, 2014)
In recent years, Google?s autonomous cars have logged thousands of miles on American highways and IBM?s Watson trounced the best human Jeopardy! players. Digital technologies?with hardware, software, and networks at their core?will in the near future diagnose diseases more accurately than doctors can, apply enormous data sets to transform retailing, and accomplish many tasks once considered uniquely human.
Includes bibliographical references and index.
Keywords: Information technology--Economic aspects